Influence of nitric oxide delivery on kidney damage in experimental model of cardiopulmonary bypass with circulatory arrest - A. M. Boyko; N. O. Kamenshchikov; A. G. Miroshnichenko; Yu. K. Podoksenov; O. N. Serebryakova; A. N. Dzyuman; Yu. S. Svirko; O. N. Dymbrylova; V. A. Lugovskiy; M. L. Diakova; D. S. Panfilov; B. N. Kozlov (Фундаментальная и клиническая медицина, 2023)
Aim. To evaluate the efficiency and safety of nitric oxide delivery for kidney protection in the simulation of cardiopulmonary bypass and circulatory arrest in the experiment.Materials and Methods. We performed an experimental modeling of cardiopulmonary bypass with circulatory arrest in 20 sheep of the Altai breed weighing 30-32 kg. Circulatory arrest was performed at moderate hypothermia (30-32°C) for 15 minutes and was followed by reperfusion and warming up to 37°C. Animals were divided into 2 equal groups: 10 sheep which received nitric oxide (NO) through the inhalations supply and cardiopulmonary bypass machine at a dose of 80 ppm, and 10 control sheep. We further collected biological fluids and tissue specimens for subsequent assessment of the safety of NO use and its nephropro-tective properties.Results. The proposed method of NO therapy during the cardiopulmonary bypass with circulatory arrest was safe and did not lead to an increase in toxic metabolites. In sheep which received NO therapy, the average concentration of NO2 throughout the entire period of the experiment was 1.2 ± 0.19 ppm (with a maximum allowable concentration of 3.0 ppm), and the concentration of methemoglobin (MetHb) was 2.3 ± 0.34% (with a maximum allowable level of 5.0%). Neutrophilic gelatinase-associated lipocalin (NGAL) was significantly lower in sheep which received NO therapy (0.67 ± 0.255 ng/mL versus 2.23 ± 0.881 ng/mL in the control group, p = 0.0001). Acute kidney injury was mitigated in sheep which received NO therapy.Conclusion. Experimental delivery of NO at a dose of 80 ppm during the cardiopulmonary bypass and circulatory arrest is safe and is associated with reduced acute kidney injury.